Seismic vulnerability of masonry Jack arch slabs. (July 2017) - Ozdemir, Muhammed Alperen; Kaya, Ercan Serif; Aksar, Bora; Seker, BurcinSenol; Cakir, Ferit; Uckan, Eren; Akbas, Bulent
Abstract: After the industrial revolution, the use of jack arch slabs (JAS) was quite common in many historical structures with the availability of iron and steel in structural engineering field. JAS is a composite system of steel I-beams and masonry bricks, which are placed between steel I-beams. This study focuses on the structural failures and weaknesses of masonry structures with JAS. The aims of this paper are to deeply illustrate the structural vulnerability of masonry JAS and to summarize the positive and negative effects of JAS on structural behavior. Within the scope of this study, this study focuses on historical American Boarding School for Girls in Merzifon, Turkey, which has one-way masonry JAS. It essentially assesses the structural behavior of the school and investigates the seismic vulnerability of JASs. For this purpose, the mechanical properties of the structural materials have been primarily evaluated with experimental tests. Then the finite element analyses have been carried out with the use of three dimension numerical model in order to investigate the structural behavior of the structure. Highlights: Structural failures & weaknesses of masonry structures with jack arch slab (JAS) are investigated Structural vulnerability of masonry JAS and positive-negative effects of JAS on structural behavior are elaborated Seismic performance and behavior of a historical masonry structure located in Anatolia, with one-way masonry JAS, is studied Mechanical properties of the structural materials are evaluated due to experimental tests Finite element analysis of the structure is carried out in order to investigate the structural behavior